1998
DOI: 10.1115/1.2842231
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Induced Wear in Steam Generator Tubes—Prediction Versus Operational Experience

Abstract: Many nuclear steam generators have accumulated more than 10 effective-full-power-years of operation. Eddy-current inspections revealed that a number of these steam generator tubes, notably those located in high local cross-flow regions, have indications of wear at some support plate elevations after 5 to 10 yr of effective-full-power operations. In the last 5 yr, a number of technical papers on nonlinear tube bundle dynamics has been published to address the effect of tube and support plate interactions. At th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 2 publications
0
9
0
1
Order By: Relevance
“…Bei Turbulenzerregung steigen die Amplituden nahezu linear mit der Anströmgeschwindigkeit an, so daß erhöhte Amplituden über Ähnlichkeitsbetrachtungen reduziert werden können. Schäden infolge von Turbulenzerregung bestehen meist in erhöhtem Abrieb an den Lagerstellen im Leitblech [AuY98,Ble79,Ble85,Cha87,Che85,KoP84]. Zur Absicherung ist jedoch die Kenntnis eines Turbulenzspektrums in der betrachteten Konfiguration notwendig [VDI97].…”
Section: Erregermechanismenunclassified
“…Bei Turbulenzerregung steigen die Amplituden nahezu linear mit der Anströmgeschwindigkeit an, so daß erhöhte Amplituden über Ähnlichkeitsbetrachtungen reduziert werden können. Schäden infolge von Turbulenzerregung bestehen meist in erhöhtem Abrieb an den Lagerstellen im Leitblech [AuY98,Ble79,Ble85,Cha87,Che85,KoP84]. Zur Absicherung ist jedoch die Kenntnis eines Turbulenzspektrums in der betrachteten Konfiguration notwendig [VDI97].…”
Section: Erregermechanismenunclassified
“…Later, a parameter named as work rate is defined, which relates to local loads and sliding distances based on the energy dissipation. 5 To predict the time history of the maximum wear depth of the tube, the wear coefficient and work rate should be obtained. Large number of research works can be found on the wear coefficient from the view point of material properties.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on SG tube mainly focused on cracks 8 and internal local wall thinning, 9 and relatively few studies have been carried out on material loss or removal phenomena caused by flow-induced vibration (FIV) and contact between tubes and support structures. 10,11 These studies were conducted for traditional components, so axial force, internal pressure or bending moment was only taken into account for typical loading conditions on the SG tubes. The studies, which were related to worn or corroded pipelines, have been applied especially to offshore engineering field.…”
Section: Introductionmentioning
confidence: 99%